Kimura's disease - Manish Swarnkar (Formosan Journal of Surgery, 2018)
Kimura's disease (KD) is a benign chronic inflammatory disorder attributed to an immune-mediated hypersensitivity which often presents as a tumor-like swelling in the head and neck region with or without lymphadenopathy, associated with hypereosinophilia and elevated serum immunoglobulin E. Most cases have been described predominantly in Chinese and Japanese people. KD has been confused with angiolymphoid hyperplasia with eosinophilia, from which it probably should be distinguished as a separate entity. The course is usually benign except for the potential cosmetic disfigurement. The diagnosis may be suggested by a fine-needle aspirate but is established by a biopsy. A case of KD in a 42-year-old male with recurrent left submandibular swelling is presented together with a brief review of the literature.